Perioperative Clinical Results of Transcervical and Transhiatal Esophagectomy versus Thoracoscopic Esophagectomy in Patients with Esophageal Carcinoma: A Prospective, Randomized, Controlled Study - Yin Z; Yang RM; Jiang YQ; Chen Q; Cai HR (International Journal of General Medicine, 2022)
Zhe Yin,1,* Ren-Mei Yang,1,* Yue-Quan Jiang,1 Qi Chen,2 Hua-Rong Cai1 1Department of Thoracic Surgery, Chongqing University Cancer Hospital, Chongqing Cancer Hospital, Chongqing, 400030, People’s Republic of China; 2Department of Anesthesiology, Chongqing University Cancer Hospital, Chongqing Cancer Hospital, Chongqing, 400030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hua-Rong Cai, Department of Thoracic Surgery, Chongqing University Cancer Hospital, Chongqing Cancer Hospital, No. 181 Hanyu Road, Shapingba District, Chongqing, 400030, People’s Republic of China, Tel +86 15523501699, Email huarongcai180@163.comBackground: This study assessed the efficacy of transcervical and transhiatal esophagectomy versus thoracoscopic esophagectomy in patients with esophageal carcinoma (EC).Methods: A total of 80 patients with EC were enrolled in this study, including 40 cases in the observation group that received transcervical combine transhiatal esophagectomy and the rest 40 cases of the group that underwent thoracoscopic esophagectomy. The preoperative, intraoperative, and postoperative data were analyzed between the two surgeries, regarding perioperative bleeding, the total number of dissected mediastinal lymph nodes, operative time, number of lymph nodes in the left para-recurrent laryngeal nerve (para-RLN) or the right para-RLN, time in the intensive care unit (ICU), postoperative pain score, the length of postoperative stay (LOPS), PO2/fraction of inspired oxygen (PO2/FiO2), pulmonary infection, and lymphatic metastasis.Results: The operations were successfully performed in all 80 patients. The results showed that patients who underwent transcervical and transhiatal esophagectomy had shorter operations than those with transthoracic esophagectomy (200 minutes vs 235 minutes, Kruskal–Wallis test [Z] = – 3.700, P < 0.001). The number of dissected mediastinal lymph nodes in the left para-RLN in the observation group was higher than in the control group (25.0% vs 2.5%, Z = 2.568, P = 0.010). The postoperative pain score day 1 (0.0% vs 17.5%, Z = – 4.292, P < 0.001), postoperative pain score day 3 (12.5% vs 37.5%, Z = – 3.363, P < 0.001) and 48-h PO2/FiO2 (290 minutes vs 255 minutes, Z = 3.747, P < 0.001) were significant between the two groups. The LOPS of patients with EC in the observation group was shorter than the control group (7 vs 8, Z = – 2.119, P = 0.034). The number of patients receiving transcervical and transhiatal esophagectomy that developed postoperative pulmonary infections was less than the controls (chi-square [χ2] = 4.114, P = 0.043). Moreover, the transcervical and transhiatal esophagectomy was an independent protect factor for postoperative pulmonary infection (odds ratio [OR] =7.801, P = 0.037).Conclusion: The transcervical and transhiatal esophagectomy is a good operation for treating patients with EC, which may offer an opportunity to treat cases who cannot have thoracotomy.Keywords: esophageal carcinoma, transcervical and transhiatal esophagectomy, thoracoscopic esophagectomy, efficacy, esophagectomy